2011
DOI: 10.1103/physrevd.84.087704
|View full text |Cite
|
Sign up to set email alerts
|

Unbreaking chiral symmetry

Abstract: In Quantum Chromodynamics (QCD) the eigenmodes of the Dirac operator with small absolute eigenvalues have a close relationship to the dynamical breaking of the chiral symmetry. In a simulation with two dynamical quarks, we study the behavior of meson propagators when removing increasingly more of those modes in the valence sector, thus partially removing effects of chiral symmetry breaking. We find that some of the symmetry aspects are restored (e.g., the masses of ρ and a1 approach each other) while confining… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 32 publications
4
88
0
2
Order By: Relevance
“…However, there are some contrary observations that chiral restoration does not immediately mean the quark deconfinement. For example, "hadrons" can be observed as bound states after removal of low-lying Dirac modes [8]. Also, it is shown that low-lying Dirac modes are not important for confinement properties such as the Polyakov loop and the linear confining potential of a quark-antiquark system [9].…”
Section: Introductionmentioning
confidence: 94%
“…However, there are some contrary observations that chiral restoration does not immediately mean the quark deconfinement. For example, "hadrons" can be observed as bound states after removal of low-lying Dirac modes [8]. Also, it is shown that low-lying Dirac modes are not important for confinement properties such as the Polyakov loop and the linear confining potential of a quark-antiquark system [9].…”
Section: Introductionmentioning
confidence: 94%
“…(Also, "hadrons" appear without low-lying Dirac modes [22], suggesting survival of confinement.) In our studies, we just consider the mathematical expansion by eigenmodes of the Dirac operator D = γ μ D μ .…”
Section: -P2mentioning
confidence: 99%
“…We use quenched Lüscher-Weisz gauge field configurations on a 20 4 lattice with β = 7.552, corresponding to the lattice spacing a = 0.2 fm, Ref. [13].…”
Section: Lattice Setupmentioning
confidence: 99%
“…In this contribution we present our first results for the Overlap quark propagator in Coulomb gauge using quenched Lüscher-Weisz gauge field configurations on a 20 4 lattice. We also briefly discuss the effect of artificial chiral symmetry restoration on the quark propagator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation